2020
DOI: 10.1016/j.mporth.2019.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Correction of neurological deformity in the foot and ankle

Abstract: Deformities of the foot and ankle in neuromuscular conditions are often complex and occur at multiple levels. Careful examination of the patient is key to identifying the deformity, and whether it is flexible or fixed. This will help to guide management options. This paper outlines treatment options for the common deformity patterns seen in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…brevis, especially if tendon transfer is to be considered. Silfverskiold testing should be performed, however it should be noted that Beckman, et al demonstrated that less than 25% of CMT patients within their cohort had a true gastrocnemius-soleal derived equinus [34].…”
Section: Osseous Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…brevis, especially if tendon transfer is to be considered. Silfverskiold testing should be performed, however it should be noted that Beckman, et al demonstrated that less than 25% of CMT patients within their cohort had a true gastrocnemius-soleal derived equinus [34].…”
Section: Osseous Proceduresmentioning
confidence: 99%
“…Those with flexible deformity should be considered for tendon transfer and osteotomy and those with fixed deformity should be considered for joint fusion, osteotomy, and soft tissue rebalancing [34]. As with pes planus, those with advanced BMI or underlying joint arthrosis, procedure selection may need to be biased toward arthrodesis for optimal outcomes.…”
Section: Osseous Proceduresmentioning
confidence: 99%
“…At this point, an aggressive Hoke Achilles lengthening is performed using a #15 blade through the arthroscopic portals. 6 The goal is to cause near-complete release of the Achilles tendon, but if there is severe contracture, a complete transection can be performed. Manual stretch is applied after to gain dorsiflexion.…”
Section: Surgical Technique (With Video Illustration)mentioning
confidence: 99%
“…Cavus is the foot deformity described as a high plantar arch and a xed forefoot equinus (1). Congenital cavus foot deformity (congenital =present at birth) is a disease very disabling that could connected to the mobility, neurologic entities and the imbalance of synergistic intrinsic and extrinsic muscles of the patients, and the problem is even dynamic (often progressive) (1)(2)(3). When the cavus foot has become a rigid posture, surgical options become more limited (3,4).…”
Section: Introductionmentioning
confidence: 99%